2(x^2-7x/2+1/2)=0
2((x-7/4)^2-49/16+1/2)=0
2(x-7/4)^2-41/8=0
(x-7/4)^2=41/16
x-7/4=±√41/4
x=(7±√41)/4
2006-10-24 19:51:06
·
answer #1
·
answered by Oo蒹葭oO 1
·
0⤊
0⤋
You want an expression like (ax+b)^2 to come out 2x^2 - 7x + z;
This must be like (x*â2 - b)^2, which when expanded is 2x^2 - 2â2bx + b^2. The middle term must be -7x, so 2â2*b = 7, so b = 7/(2â2). The binomial squared becomes (xâ2 - 7/2â2)^2 = 2x^2 - 7x + 49/8; The difference between this and the expression you were given is 1-49/8; add that to the expression you have and you will "complete the square" to get (xâ2 - 7/2â2)^ + 1 - 49/8; when you expand the square of the binomial, the last term will be 49/8, which will cancel with the -49/8, leaving the 1. So your equation is now
(xâ2-7/2â2)^2 = 49/8-1; take the square root of both sides:
xâ2 - 7/2â2 = ±â(49/8-1)
xâ2 = 7/2â2 ± â(49/8-1)
x = 7/4 ± â[(49/8-1)/2]
2006-10-25 03:15:30
·
answer #2
·
answered by gp4rts 7
·
0⤊
0⤋
2x^2 - 7x + 1 = 0
x^2 - 7/2x + 1/2 = 0
equation of the form a^2 + 2ab + b^2 = 0 => (a + b)^2 =0
to generate the perfect square 2ab = -7/2 and a=1 so b = -7/4
then we have to add (-7/4)^2 to both sides of the equation
x^2 - 7/2 x +(-7/4)^2 = (-7/4)^2 - 1/2
(x - 7/4)^2 = 49/16 - 1/2 = 41/16
the solution will be:
x - 7/4 = +/- sqrt(41/16)
x will have 2 solutions:
x = 7/4 + sqrt(41)/4 or x = 7/4 - sqrt(41)/4
2006-10-25 03:12:45
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
2x^2 - 7x + 1 = 0
x^2 - (7/2)x + 1/2 = 0
x^2 - (7/2)x + (7/4)^2 -(7/4)^2 = -1/2
(x - (7/4))^2 = -1/2 + 49/16
(x - 7/4) = ±sqrt(49/16 - 8/16)
x = (7 ± sqrt(41))/4
x = ( 0.14922, 3.35078)
2006-10-25 02:56:36
·
answer #4
·
answered by Helmut 7
·
0⤊
0⤋
2x^2-7x+1=0
x^2-7x/2+1/2=0
x^2-7x/2 = -1/2
x^2-7x/2+49/16=-1/2+49/16
(x-7/4)^2=41/16
x-7/4=+-sqrt(41/16)
x=7/4+-sqrt(41/16)
x=1/4(7+-sqrt(41))
2006-10-25 03:06:40
·
answer #5
·
answered by mekaban 3
·
0⤊
0⤋
x= (7 + â41)/14
and
x= (7 - â41)/14
2006-10-25 02:49:04
·
answer #6
·
answered by Sergio__ 7
·
0⤊
0⤋
(â2*x - 7/(2â2))^2 - (7/(2â2))^2 + 1 = 0
(â2*x - 7/(2â2))^2 = + (7/(2â2))^2 - 1
etc etc.
2006-10-25 03:46:30
·
answer #7
·
answered by gjmb1960 7
·
0⤊
0⤋
by formula -b+- root( ( b^2-4ac))/2a
7+root ((49-8))/4
( 7+6.41)4
= 3.3525
- 059/4
0 .1475
x= 3.3525 or 0.1475
2006-10-25 02:51:40
·
answer #8
·
answered by pramod bhat 1
·
0⤊
1⤋